Behavior of introduced regional clones of theobroma cacao toward the infection moniliophthora roreri in three different regions of colombia (2011)
Moniliasis (frosty pod rot), caused by Moniliophthora roreri, is the most limiting disease of cacao bean production in Colombia. Disease control has focused primarily on the implementation of cultural methods, which are inefficient and increase costs of production. A promising alternative for the control of M. roreri is the genetic approach, involving the search for plants with known resistance in the field. The aim of this study was to evaluate the behavior of 13 regional clones of Corpoica Selection Colombia (SCC), ten regional Fedecacao clones (with the initial F), three clones Caucasia (CAU) and 13 introduced clones for resistance to M. roreri, by monitoring symptoms and signs of the pathogen in fruits of the cacao at three experimental sites located in Arauquita (Arauca), San Vicente and Rionegro (Santander). To estimate the degree of susceptibility or resistance of each clone, the pathogen was inoculated into fruits 75-5 days old. Eight weeks later, the variables Incidence, Internal Severity Index and External Severity Index were evaluated. In the three experimental sites, the ICS clone 95 behaved as a resistant plant with ISI ranging from 1.4 to 1.9. In the other clones tested, susceptibility varied according to altitude and environmental conditions. However, the ICS clone 95 showed partial resistance, varying the spread of the pathogen in the plant tissue.